China and India: socio economic performance and prospects - Etienne, Gilbert (New Delhi, 1995)
There have been many studies comparing the socio-economic performance of China and India since the early 1950s. The basic differences in the political and economic systems of the two countries affected the growth of their economies and institutions differently, though most of the problems were common. Generally Western commentators, despite their criticism of the Chinese political system, tended to present a more favourable picture of the socio-economic progress in China than that in India. The rapid economic growth in China since the reforms were started in China in 1980, made this comparison sharper. With the introduction of substantive reforms in India in 1991 and the growing experience with the working of reforms and institutions in both the countries, there is, in recent times, a more realistic assessment.
Keywords: Rajiv Gandhi foundations